Biosensors, memristors and actuators in electrical networks of plants. Issue 1 (2nd January 2017) - Volkov, Alexander G.
Abstract: Electrical circuits connect biosensors and actuators in plants and trees. There are many electrochemical components and devices in plants created by nature. Memristors participate in the electrical signal transduction between phytosensors and actuators. Electrical processes play important roles in the physiology of plants, trees, fruits and seeds. Electrical form of energy has no entropy content that can be used to do work, information transfer, computing and analysis. These signals propagate along sophisticated electrical circuitry of plants consisting of many electrical components and cell computing system for decision-making processes. Action potentials are the mediators for intercellular and intracellular communication in response to environmental stresses. Abstract :